Socio-economic inequality, interregional mobility and mortality among cancer patients: A mediation analysis approach. (August 2022) - Rubino, Claudio; Di Maria, Chiara; Abbruzzo, Antonino; Ferrante, Mauro
Abstract: This paper investigates the effect of socio-economic status on interregional mobility and mortality among cancer patients. The cohort under analysis comprises patients residing in Sicily (Italy), who were diagnosed with lung and colon cancer between 2010 and 2011. The data was collated from the hospital discharge records of the Sicilian Region and the Regional register of the causes of death, by considering all those patients for whom information relating to socio-economic status was available. First, graphical models were applied to highlight the multivariate structure of association among socio-economic status, interregional mobility and 3-year mortality. Secondly, mediation analysis quantified the direct and indirect effect of socio-economic status relating to mortality. The results revealed that socio-economic status is associated directly and indirectly with mortality due to lung cancer, mediated by interregional mobility. On the other hand, the association of socio-economic status with mortality from colon cancer is only indirect, and also mediated by interregional mobility. The authors of this research hold that the extent of patient mobility and its relation to mortality call for a reconsideration of health policy. Highlights: An analysis of socio-economic status, inter-regional mobility and mortality among cancer patients. Graphical models permit the detection of the complex structure of relationships between the considered phenomena. Causal mediation analysis facilitates the quantification of indirect effects of socio-economic status. Policy considerations arise concerning equal access to healthcare.